Increase Writing Performance using A Shaping Procedure with a Patient with Sequelae Caused by Cardiovascular Accident - Renaux Charlotte; Rivière (BCBA-D) Vinca; Joëlle Nuchadee (BCBA) M.L. (Journal of Aging Research And Healthcare, 2017)
Background and Objective: Behavioral procedures have proven to be effective with elderly adults in nursing home. The purpose of this study was to evaluate the effectiveness of a shaping procedure as a means of increasing writing performance. More specifically, our aim was to reeducate a motor behavior in a patient for whom the behavior was no longer present. Materials and Methods: The participant was an elderly (76-year-old) who had sequelae from a cardiovascular accident since 2011, and was asked to write some selected words. Data were collected though face-to-face interviews then analyzed using cotation methods. Results: The shaping and chaining procedures were efficient and performance of writing increased, even for infrequent words. Conclusion: Increasing writing performance is possible for the elderly people, even if they have suffered from cardiovascular accidents in the past. Here we used a successful brief shaping procedure to enhance quickly that ability.
Keywords: Elderly